Microwave incinerated rice husk ash (MIRHA) and used engine oil (UEO): Towards sustainable concrete production - Mohd Kamal N.L.; Beddu S.; Nuruddin M.F.; Shafiq N.; Muda Z.C. (Trans Tech Publications Ltd, 2023)
Rice is a primary source of food for billions of people and covers 1% of the earth's surface. On average 20% of the rice paddy is husk, giving an annual total production of 120 million tones. Nowadays, there are two common methods used to dispose the rice husk which is either it is being dump or burnt. Rice husk ash (RHA) which is produced by burning paddy husk led to the issue of ozone layer depletion. It also causes damage to the land and the surrounding area where it is being dumped. Previous studies have pointed out that RHA produced contains more than 80% pure silica and if properly prepared, it is in an active form which behaves very much like cement. Same goes with used engine oil (UEO). Many people are aware that UEO shouldn't be dumped, but recycled. It is incredibly toxic stuff and a gallon can contaminate one million gallons of water. Pouring it on land doesn't reduce the risk either as it can seep down into the water table.The objective of this research is to obtain an optimum percentage of inclusion of microwave incinerated rice husk ash (MIRHA) as a cement replacement and UEO in order to produce a better concrete in terms of compressive strength compared to normal OPC concrete. The test results showed MIRHA concrete performed better than normal OPC concrete and the incorporation of UEO and MIRHA in concrete showed the compressive strength give better performance. © (2014) Trans Tech Publications, Switzerland.